Public place making in Enkanini : a socio-spatial methodology for intervening on the informal - Damasceno, Tiago Rocha (School of Architecture, Planning and Geomatics, 2017)
Architectural and urban design projects implemented on informal settlements tend to neglect the local existing patterns of living. As a result, these projects impose new social and spatial conditions that are often not liberating to the communities that they serve. As an alternative, this thesis proposes a methodology that contrasts with this approach, a process that aims at understanding the socio-spatial conditions of a particular area in order to inform spatial intervention. For this purpose, this thesis will incorporate a study of the general conditions that define Enkanini, an informal settlement of Cape Town. Such conditions will consequently inform where, how and when one must implement interventions on this settlement. The outcome of this thesis will consequently not be the formal design of a singular building; but rather a series of key concepts that would guide strategic spatial intervention in Enkanini.